2004
DOI: 10.1038/sj.onc.1207765
|View full text |Cite
|
Sign up to set email alerts
|

ERβ exerts multiple stimulative effects on human breast carcinoma cells

Abstract: Recent studies of ERs in breast cancer have demonstrated the existence of ERb in addition to ERa. Some clinical data indicated that ERb had prognostic value for patient's survival, which suggested that ERb plays a key role in breast cancer development and metastasis. To test this hypothesis, we generated an ERb high-expression cell line by reintroduced human ERb cDNA into MDA-MB-435 cells. We demonstrated that ERb exerted multiple tumor-stimulative effects on human breast carcinoma cells both in vivo and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
4
51
0
Order By: Relevance
“…40 In addition, in vivo and in vitro studies have demonstrated that ERb exerts stimulative effects on breast cancer development and metastasis. 41 It has also been shown that ERb negatively affects malignant cell tumorigenesis. 19,42,43 Although to our knowledge the exact correlation between ERb expression and tumor progression in thymic epithelial tumors is still unclear, ERb is suggested as a potential target in the treatment of ERb-positive thymomas and thymic carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…40 In addition, in vivo and in vitro studies have demonstrated that ERb exerts stimulative effects on breast cancer development and metastasis. 41 It has also been shown that ERb negatively affects malignant cell tumorigenesis. 19,42,43 Although to our knowledge the exact correlation between ERb expression and tumor progression in thymic epithelial tumors is still unclear, ERb is suggested as a potential target in the treatment of ERb-positive thymomas and thymic carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Most cell line models in which ERb1 has been stably expressed either inducibly or constitutively show that overexpression of ERb1 inhibits proliferation irrespective of whether it is coexpressed with ERa (Paruthiyil et al, 2004;Strom et al, 2004;Murphy et al, 2005) or not (Lazennec et al, 2001;Cheng et al, 2004). However, two studies using cell line models have been published in which stable constitutive overexpression of ERb1 resulted in increased proliferation (Tonetti et al, 2003;Hou et al, 2004) although in the former publication the short form of ERb1 (truncated by 45 amino acids from the N-terminus) was used. Both breast cancer cell lines used (MDA-MB-231 and MDA-MB-435) are typically ERa negative and therefore can be considered to represent the ERb alone expressing breast tumours cohort in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of ERβ into ER-MDA-MB-435 and MDA-MB-231 breast cancer cells increases cell proliferation in an E2-independent manner, cell invasiveness, and metastasis [73]. In contrast, introduction of ERα into ER-breast cancer cells generally decreases their proliferation in an E2-dependent manner, and their invasiveness and migration by both ligand-dependent and ligand-independent mechanisms [74,75].…”
Section: Potential Role Of Erα/erβ Heterodimers In Biological Responsmentioning
confidence: 98%